Oral language comprehension of young adults with low-level reading comprehension - Bar-Kochva, Irit; Vágvölgyi, Réka; Schrader, Josef; Nuerk, Hans-Christoph (Frontiers in Psychology, 2023)
Significant difficulties in reading comprehension, despite attendance of compulsory schooling, are a worldwide phenomenon. While previous research on adults with low literacy skills focused primarily on their reading ability, less is known about their oral language skills. In this Brief Research Report, we present an investigation of the listening comprehension skills of a selected group of German-speaking young adults, whose reading comprehension is at a primary school level (n=32, ages 16 to 19 years). In addition, the relationship between listening comprehension and reading comprehension, beyond word reading skills, was tested. Standardized tests of reading and listening comprehension in the German language were administered. The average performance of the group in the listening comprehension tasks was below the level expected by age and educational level. In addition, when entered into a stepwise regression equation, listening comprehension, but not word reading, explained a significant amount of variance in reading comprehension. This pattern of relationship differs from previous findings in studies of adults struggling to read the opaque English orthography. Whether orthographic transparency explains this discrepancy should be further tested in cross-orthography studies with larger samples of adults with low literacy skills.